Survey of Micro, Small, and Medium Enterprises in Agri-Food Value Chains: Network-Based Recruitment Approach in Bangladesh - International Food Policy Research Institute (International Food Policy Research Institute, 2024)
The datasets and questionnaires in this package come from the second phase of IFPRI's "Digital Financial Services Adoption among SMEs in the Midstream of Agricultural Value Chains" project. This phase focused on midstream actors in the rice and potato value chains in Bangladesh, using tailored surveys to explore their financial capabilities and constraints. The surveys were conducted between June and August 2023 in the Bogra and Rangpur districts. The data collection was iterative, designed to capture insights from intermediary actors across different segments of the agri-food value chain. In randomly selected villages within our primary study areas, a brief farmer survey was used to identify intermediary actors they had sold commodities to in the last 30 days. These identified intermediaries were then contacted and interviewed using a more comprehensive survey. In Bangladesh, 280 rice farmers and 254 potato farmers participated in the farmer surveys. For the midstream actors, the sample includes 1,066 traders, 456 processors, and 220 wholesalers in the rice value chain, and 1,117 traders, 1 processor, 235 wholesalers, and 1 aggregator in the potato value chain.